(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines the role of reflection and self-assessment mechanisms in the development of student portfolios. The research analyzes how students utilize reflective practices to critically evaluate their learning processes and enhance competencies through self-assessment. Employing both qualitative and quantitative methodologies, the study assesses the effectiveness of reflection strategies in portfolio formation. Findings highlight that reflection and self-assessment significantly contribute to fostering independent thinking skills and improving academic performance among learners.